Whale watching in Los Cóbanos, El Salvador: a first approach to the activity - Castaneda, Melvin Giovanni; Vázquez Cuevas, Marlenne; Flores Escalante, Álvaro Humberto; Salgado López, José Dagoberto (Realidad y Reflexión, 2021)
In El Salvador, cetaceans have been little studied. Due to their regular migratory habits and association with the coasts; some species such as the humpback whale have been the focus of whale watching tourism in recent years. This type of tourism is growing rapidly around the world: one of its challenges is to conserve habitat and species while managing the needs of communities. Aspects of tourist activity and species are still unknown, being essential to generate scientific information. The objective is to describe the tourist activity of whale watching in the community of Los Cóbanos during November 2014-April 2015, taking as elements the description of the tourist supply and demand, estimate of the economic cost and species object of the activity. This work represents the first efforts to document socioeconomic aspects of whale watching tourism and lays the foundations for the conservation of these species in the country. En El Salvador, los cetáceos han sido poco estudiados. Por sus hábitos migratorios regulares y asociación a las costas, algunas especies como la ballena jorobada son foco del turismo de avistamiento de cetáceos en años recientes. Este tipo de turismo crece rápidamente alrededor del mundo: uno de sus retos es conservar el hábitat y las especies mientras se manejan necesidades de las comunidades. Aún se desconocen aspectos de la actividad turística como de las especies, siendo indispensable generar información científica. El objetivo es describir la actividad turística de avistamiento de cetáceos en comunidad de Los Cóbanos durante noviembre 2014-abril 2015, tomando como elementos la descripción de la oferta y demanda turística, estimación del costo económico y especies objeto de la actividad. Este trabajo representa los primeros esfuerzos por documentar aspectos socioeconómicos del turismo de avistamiento de cetáceos y asienta las bases para la conservación de estas especies en el país.